(untitled) (BIRDEM Medical Journal, 2022)
Background: Diabetic myonecrosis is an under-reported complication of long-standing, poorly controlled diabetes mellitus. It is usually a self-limiting condition and responds well to conservative management. Patients with diabetic myonecrosis frequently have other microvascular complications. Although the short-term prognosis is good, the long-term prognosis is poor. Less than 200 cases have been reported in the literature since it was first described 46 years ago. There is no clear ‘standard of care’ for managing these patients. Due to a lack of awareness, the diagnosis is often missed, resulting in unnecessary and deleterious interventions such as antibiotics, muscle biopsies and surgery which can complicate the recovery. We report six cases of diabetic myonecrosis admitted in a tertiary care hospital; all of them recovered well by conservative measures like analgesics and bed rest. Our report aims to emphasize the importance of early diagnosis of diabetic myonecrosis and to find out the pattern of clinical, biochemical and radiological profiles among the myonecrosis cases. Methods: Patient’s socio-demographic, clinical, laboratory data were recorded systemically in case-record forms after obtaining informed written consent from patients or attendants over four years from 2018 to 2021. Result: We report six cases of diabetic myonecrosis managed in a tertiary care hospital over four years. Five of the cases were female and all had type 2 diabetes mellitus, with a mean duration of diabetes was 14.5 years.The presentation was acute in four patients and sub-acute in another two patients. All these patients had poorly controlled diabetes mellitus; the average HbA1c was 10.8%. Microvascular complications of diabetes mellitus were found in all the cases. Conclusion: Diabetic myonecrosis is an underdiagnosed complication of diabetes mellitus. It should be considered in the differential diagnosis for diabetic patients who present with painful swollen muscles. A high index of suspicion requires for the diagnosis, which avoids unnecessary intervention. BIRDEM Med J 2022; 12(2): 147-151